Pedagogical Practices of Tutors at DMMMSU Open University System - Carrera, Jonald Fontanilla (ASEAN Journal of Education, 2019)
Pedagogical practices support students’ learning. This is in line with the dynamic teaching pedagogy that facilitates student’s professional growth and career advancement. In so doing, classroom teaching models are introduced to spearhead the needs of the students along their way to a higher career choice. Quality education rests primarily on the ability of the teachers to deliver quality instructional performance. It has been said that the best instructional medium inside the classroom is the teacher. It is imperative then that the teacher is equipped with an outstanding or excellent personal facility and teaching attributes that ensure effective teaching and learning outcomes that contribute immensely to the attainment of quality education. The study assessed the pedagogical practices of tutors at DMMMSU Open University System. The descriptive method was used in this study. The primary instrument used in gathering data was the two-part guide questionnaire. Data were collected, tallied and analyzed in accordance with the study. The quantitative data were analyzed using mean under the Microsoft Analysis Tool Pack. In light of the findings of the study, the pedagogical practices of tutors were globally competitive and highly recommended for quality distance learning education at its finest, the stakeholders and the clientele were key components for quality distance learning education, and the formulation of an enhancement program contributed to the sustainability of the best instructional practices of DMMMSU Open University System.